2011
DOI: 10.1111/j.1742-6723.2011.01419.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for sedation‐related events during procedural sedation in the emergency department

Abstract: Sedation-related events, especially airway events, are common but very rarely have an adverse outcome. Elderly patients, deeply sedated with short-acting agents, are at particular risk. The results will help tailor sedation to individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 35 publications
3
45
1
Order By: Relevance
“…However, a prospective multicentre emergency department study of 2623 patients by Taylor et al 15 revealed 461 patients experienced at least one airway event requiring intervention. Only one of the 34 patients who vomited developed aspiration pneumonia following sedation use.…”
Section: Discussionmentioning
confidence: 99%
“…However, a prospective multicentre emergency department study of 2623 patients by Taylor et al 15 revealed 461 patients experienced at least one airway event requiring intervention. Only one of the 34 patients who vomited developed aspiration pneumonia following sedation use.…”
Section: Discussionmentioning
confidence: 99%
“…The present study aimed to determine the nature of contemporary procedural sedation practice in Australian EDs. The results, in conjunction with other components of the project including adverse events 28 and failed procedures, 29 will inform the development of Australian PSA guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…5 Ketamine administered by intravenous or intramuscular routes, even as a single drug, has been indicated as a safe and effective alternative for rapid analgesia. 6,10,27,28 In a systematic review of randomized trials of analgesia and sedation for reduction of fractures in children at a PEU, ketamine/ midazolam proved to be more effective as an analgesic and had fewer adverse effects than combinations of fentanyl/midazolam or propofol/midazolam. 1,2,4,5,15,25 When the level of satisfaction of parents and orthopedists were analyzed with analgesia for the orthopedic procedure, it was found that levels were quite high.…”
Section: Discussionmentioning
confidence: 99%